UPAYA MENINGKATKAN KEMAMPUAN MEMBACA NYARING MENGGUNAKAN MEDIA PUZZLE DALAM MODEL PEMBELAJARAN PROBLEM BASED LEARNING SISWA KELAS III SDN PULUHAN - Denya Pradhesta Narakundi; Bahtiyar Heru Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to determine how well grade III students at Puluhan State Elementary School can read aloud when employing puzzles in the Problem-Based Learning (PBL) model. This study is a Classroom Action Research (CAR). The subjects consisted of 23 grade III students, including 11 male and 12 female students. Data were collected through observation and oral tests. The data analysis technique used was quantitative. Quantitative techniques were employed to manage the quantitative data in the form of student test results and observations of the implementation of learning. The results of the pre-cycle study showed 48% mastery and 52% non-mastery among the students. In Cycle I, there was an increase, with 70% mastery and 30% non-mastery. In Cycle II, a significant improvement was observed, with 87% mastery and only 13% non-mastery. Therefore, using puzzle media in the PBL model can improve the reading aloud skills of third-grade students at SDN Puluhan.